Love beyond gluten: self-esteem, illness identity, and social support in romantic rejection concerns among adolescents with celiac disease - Shani, Maor; van Zalk, Maarten H. W. (Frontiers in Psychology, 2024)
Introduction Fear of stigmatization, high perceived partner burden, or refraining from self-disclosure may manifest in romantic rejection concerns among adolescents with celiac disease (CD), potentially impacting their health-related quality of life (HRQOL). This study examined the prevalence, predictors, and consequences of romantic rejection concerns among adolescents and young adults with CD. Methods A cross-sectional online survey was conducted among 165 German adolescents and young adults (aged 14–22) with self-reported CD. Participants completed measures of romantic rejection concerns, illness identity, self-esteem, peer support, and CD-specific HRQOL. Results Participants reported moderate levels of concerns about the impact of CD on their romantic relationships, with no significant gender differences. Participants involved in romantic relationships expressed lower concerns of rejection, but similar preference for a “gluten-free partner.” Hierarchical regression analysis revealed that higher illness acceptance and peer support predicted lower rejection concerns. Significant interactions emerged between self-esteem and illness acceptance, and between self-esteem and peer support. Higher illness acceptance predicted fewer rejection worries only among those with high self-esteem, while peer support played a mitigating role only for those with low self-esteem. Romantic rejection concerns significantly predicted lower CD-specific HRQOL across all domains. Discussion Anxieties about CD's impact on romantic relationships are prevalent among adolescents and may hinder their HRQOL. The findings highlight the complex interplay between self-esteem, illness identity, and social support in shaping romantic concerns. Targeted interventions focusing on peer support and fostering positive illness identity are recommended to alleviate rejection fears and improve HRQOL among youth with CD.